Women Empowerment Through Microcredit: A Study on Small Unit (Group) of Two Leading Microcredit Organizations in Savar Upazila : (Bangladesh Journal of Public Administration, 2022)
For the time being, efforts are continued by the different organizations of Bangladesh to empower rural women who were so vulnerable in their premises that no money-lending organization trusted them. For the last few decades, microcredit – collateral-free credit support has been disbursed for the betterment of women and their empowerment. This research investigates the contribution of microcredit to empower rural women and how they are facilitated by nourishing it. The perceptions of female borrowers are also assessed here. Following the qualitative method, 46 female credit borrowers equally from two groups are selected purposively for the collection of firsthand data while different credible secondary sources are searched for extra information. Both the groups ensure equal representation from Bangladesh Rural Development Board (BRDB) and Bangladesh Rural Advancement Committee (BRAC). The study contributes to understanding the scenario of the group members as a small unit of microcredit. The updated findings of empowerment and self-dependency of women by dint of existing system of microcredit program are also helpful for the policy formulation at the group level. The result unveils that microcredit and its group activities improve income and savings of female borrowers that entails declining domestic violence. In some contexts, the ability to take part in the decision-making process of personal and family life is achieved. But in most of the parts, microcredit improves different essential skills of credit beneficiaries to strengthen their morale. Finally, the study finds that the women perceive more empowered after the inflow of microcredit in their everyday activities. Therefore, some pragmatic recommendations based on the findings are proposed for better women empowerment in rural areas.